2018
DOI: 10.1007/s10147-018-1250-2
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio as an early marker of outcomes in patients with advanced non-small-cell lung cancer treated with nivolumab

Abstract: BackgroundThere is an unmet need to identify markers that predict the response to nivolumab in patients with non-small-cell lung cancer (NSCLC). The neutrophil-to-lymphocyte ratio (NLR) was recently recognized as an indicator of a poor prognosis in patients with various cancers. In the present study, we quantified the predictive impact of NLR in patients with NSCLC treated with nivolumab.MethodsWe retrospectively analyzed 101 patients with advanced NSCLC treated with nivolumab at Kansai Medical University Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 31 publications
8
87
0
2
Order By: Relevance
“…Seven studies 1719,26,29,30,33 reported number of patients achieved ORR and DCR after treatment of Nivolumab (Supplemental Table 3). In a total of 716 patients, 141 were considered as ORR and 236 as DCR, with percentages of 19.69% and 32.96%, respectively.…”
Section: Combined Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies 1719,26,29,30,33 reported number of patients achieved ORR and DCR after treatment of Nivolumab (Supplemental Table 3). In a total of 716 patients, 141 were considered as ORR and 236 as DCR, with percentages of 19.69% and 32.96%, respectively.…”
Section: Combined Resultsmentioning
confidence: 99%
“…38 Meanwhile, Nivolumab and Pembrolizumab are the recently approved immune checkpoint blockades for treating advanced non-small cell lung cancer after failure of traditional chemotherapy or not. 3 Several clinical studies 17,18,20,39 assessed relationship between NLR and immunotherapy, and some of them 17,18,20 argued that NLR could serve as a predictive factor while other found negative results. 39 Could NLR be a candidate for predicating prognosis of Nivolumab in NSCLC?…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that low baseline NLR and ANC predict the efficacy of nivolumab therapy in various cancers . More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy . NLR and ANC have been reported to correlate with the number of circulating MDSCs and tumor‐associated neutrophils, which suppress the function of antitumor T cells .…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not clarify the mechanisms that created these synergistic effects during nivolumab treatment. Several studies have shown that the neutrophil‐to‐lymphocyte ratio (NLR) and the absolute neutrophil count (ANC) in the blood can predict the efficacy of PD‐1 inhibitors in patients with NSCLC . NLR and ANC have also been reported to reflect the number of circulating myeloid‐derived suppressor cells (MDSCs) and tumor‐associated neutrophils, which inhibit the function of antitumor T cells .…”
Section: Introductionmentioning
confidence: 99%
“…Patients were dichotomized according to prespecified cutoff values of NLR ≥3 (high NLR [H‐NLR]) versus <3 (low NLR [L‐NLR]) and PLR ≥180 (high PLR [H‐PLR]) versus <180 (low PLR [L‐PLR]) . The cutoffs were chosen according to literature references .…”
Section: Methodsmentioning
confidence: 99%